European hospital managers' perceptions of patient-centred care: A qualitative study on implementation and context. Issue 6 (21st September 2015) - Taylor, Angelina; Groene, Oliver
Abstract : Purpose: – The spotlight has recently been placed on managers' responsibility for patient-centred care as a result of Mid Staffordshire NHS Foundation Trust failings. In previous research, clinicians reported that managers do not have an adequate structured plan for implementing patient-centred care. The purpose of this paper is to assess the perceptions of European hospital management with respect to factors affecting the implementation of a patient-centred approach. Design/methodology/approach: – In total, 15 semi-structured interviews were conducted with hospital managers ( n =10), expert country informants ( n =2), patient organisations ( n =2) and a user representative ( n =1) from around Europe. Participants were purposively and snowball sampled. Interviews were analysed using framework analysis. Findings: – Most participants felt that current levels of patient-centred care are inadequate, but accounted that there were a number of macro, meso and micro challenges they faced in implementing this approach. These included budget constraints, political and historical factors, the resistance of clinicians and other frontline staff. Organisational culture emerged as a central theme, shaped by these multi-level factors and influencing the way in which patient-centred care was borne out in the hospital. Participants proposed that the needs of patients might be better met through increasing advocacy by patient organisations and greater staff contact with patients. Originality/value: – This study is the first of its kind to obtain management views from around Europe. It offers an insight into different models of how patient-centred care is realised by management. It indicates that managers see the value of a patient-centred approach but that they feel restricted by a number of factors at multiple levels.